Narrow band imaging efficiency in evaluation of mucosal healing/relapse of ulcerative colitis - Sasanuma, Seiko; Ohtsuka, Kazuo; Kudo, Shin-ei; Ogata, Noriyuki; Maeda, Yasuharu; Misawa, Masashi; Mori, Yuichi; Kudo, Toyoki; Hisayuki, Tomokauzu; Wakamura, Kunihiko; Hayashi, Takemasa; Katagiri, Atsushi; Miyachi, Hideyuki; Baba, Toshiyuki; Ishida, Fumio (Endoscopy International Open, 2018)
Background and study aims Mucosal healing is a current treatment target in ulcerative colitis (UC), while histological remission is another target. The aim of this study was to evaluate the efficiency of magnified narrow band imaging (NBI) findings of mucosal healing and their relationship with histological activity and prognosis. Patients and methods Patients with UC who underwent total colonoscopy between January 2010 and December 2012 with left-sided or total-colitis type UC and achieved clinical remission with an endoscopic Mayo score of 0 or 1 were included. Each colon section was observed with white light and magnified NBI, with the colonoscopy being repeated at 1-year follow-up. We assessed the relationships of magnified NBI with histological disease activity and prognosis. Magnified NBI findings were divided into three categories; honeycomb-like blood vessels (BV-H), blood vessels shaped like bare branches (BV-BB), and blood vessels shaped like vines (BV-V). Results Fifty-two patients were included. The percentage of remitted mucosa with BV-BB was 37 %, while that of mucosa with scars with BV-H was 35 %. BV-H and BV-BB did not show pathological activity (12/292 and 8/299, respectively), while BV-V showed high pathological activity (27/33, 81 %). There was a correlation between magnified NBI findings and pathological findings (P < 0.01). The odds ratio for inflammation activity at 1-year follow-up was 14.2 for BV-BB (95 % CI, 3.3 – 60.9)Conclusion Magnified NBI findings showed a good relationship with histological activity. This suggests that we could estimate histological activity without biopsy, and also the possibility of predicting relapse over the following year.